Gustatory Function in Acute COVID‐19 ‐ Results From Home‐Based Psychophysical Testing. (1st March 2022) - Hintschich, Constantin A.; Brosig, Anja; Hummel, Thomas; Andorfer, Kornelia E.; Wenzel, Jürgen J.; Bohr, Christopher; Vielsmeier, Veronika
Abstract : Objective: Gustatory function during COVID‐19 is self‐reported by around 50% of patients. However, only a few studies assessed gustation using psychophysical testing during acute infection. The objective of this study is to test gustatory function on threshold tests in the very first days of COVID‐19. Methods: Psychophysical testing consisted of validated and blinded tests for olfaction (NHANES Pocket Smell Test) and gustation (Taste Strips Test). These test kits were sent to home‐quarantined patients and self‐administered using a detailed instruction sheet. Results: A total of 51 patients were included in this study. Testing was performed 6.5 ± 2.7 days after sampling of respiratory swabs. At this time 37% of patients stated to currently experience a gustatory impairment. The mean Taste Strips score was 10.0 ± 3.4 with 28% scoring in the range of hypogeusia. Interestingly, no significant difference in the results of gustatory testing could be observed between the group with subjectively preserved gustation and the group with self‐rated taste impairment. Conclusion: During the very first days of COVID‐19, psychophysical gustatory testing revealed hypogeusia in 28%. This is far lower than patients' self‐reports. Different from previous studies, we did not find clear evidence for an impairment of only certain taste qualities. Level of Evidence: 3 Laryngoscope, 132:1082–1087, 2022